Clinical observation on the efficacy and safety of skin care product containing artemisia naphtha in individuals with sensitive skin - Sha WANG; Hu HUANG; Qingchun DIAO; Kan TAO; Jing LV; Yang JIANG; Lili GUO; Ziyan QIN; Mengru GE; Jiajia LI; Ling LI; Yucan AO; et al. (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To evaluate the safety and efficacy of skin care product containing artemisia naphtha in individuals with sensitive skin. Methods A single-center and self-controlled (before and after application) clinical trial was conducted in 31 subjects with sensitive skin. Test product was applied to the face of the subjects twice daily for 4 weeks. Measurement of physiological function, VISIA-CR photography and lactic acid test were carried out on the skin before and on the days 7,14,28 of the trial. 16S rRNA gene sequencing technology was used to analyze the microecological diversity of the skin surface meanwhile physician and subject' self-assessments were performed. Results Physician assessment scores for erythema were decreased at all three follow-up visits (P<0.05 vs. baseline). The subjects' self-assessments of itching, tingling, burning, tightness, flushing and sensitivity scores were also decreased (all P<0.05 vs. baseline).The skin a* values were decreased significantly (all P<0.05 vs. baseline). Similarly, erythema index was significantly decreased (all P<0.05 vs. baseline). Moreover, stratum corneum hydration levels were significantly increased on D7 and D28 (all P<0.05 vs. baseline). The transepidermal water loss rates tended to decrease, and were significantly different between the baseline and day 14 (P<0.05). In contrast, the skin elasticity and firmness parameters were not changed significantly. Furthermore, lactic acid scores were decreased significantly on D14 and D28 (all P<0.001 vs. baseline). Additionally, there was a tendency of increases in alpha diversity indices ACE and Chao1 on days D7 and D14, with a significant increase on day 14 (P<0.05 vs. baseline). Beta diversity analysis showed that the four groups of samples failed to gather into clusters, and the differences in composition structure were not significant. No adverse reactions were observed during the trial. Conclusions Skin care product containing artemisia naphtha is safe for individuals with sensitive skin and improves multiple clinical signs and symptoms of sensitive skin, including acceleration of the skin barrier recovery, elevation in stratum corneum hydration, reduction in transepidermal water loss rates and lactate stinging test score, alleviation of itching, tingling, burning, tightness and flushing, and increases in the richness and diversity of facial skin microbiota.